GENETIC DIVERSITY AND POPULATION STRUCTURE OF THE ASIAN HOUSE RAT RATTUS TANEZUMI IN SHANXI, CHINA - X. Yang; T. Wang; H. Guo; J. Yang; M. Zhang; B. Zou; Z. Ren; J. Zhang; J. Zhang (Journal of Animal and Plant Sciences, 2022)
Asian house rat Rattus tanezumi, a common commensal rat in southern China, was first discovered in Shanxi Province, northern China, in the early 1990s. Its rapid expansion threatens to reduce the diversity of native species and poses a serious threat to local biodiversity. In this study, samples were collected from fourteen different locations using one-night trapping method, and eight populations of Rattus tanezumi were captured. Seventy-six samples were successfully genotyped at 12 microsatellite loci and 70 mitochondrial DNA (mtDNA) cytochrome c oxidase subunit I gene sequences were amplified and sequenced. The analysis of genetic diversity and population structure about R. tanezumi significantly reveal evolutionary forces and non-random mating within populations in Shanxi, which could be concluded as a bottleneck or selective sweep. The genetic and geographical distances were uncorrelated, suggesting that geographic distance had no (or a weak) effect on genetic distance. Furthermore, we found four new haplotypes that are most similar to a nonrandom subset of those in their native range in southern China. The haplotypes could be more common in Shanxi due to a genetic bottleneck or natural selection. Further evidence is needed to reveal the mechanisms of genetic exchange and molecular evolution underlying these patterns. Our results provide fundamental insights into the potential introduction routes and the relevant features of successful invasions.
Keywords: Diversity; Population structure; Asian house rat; Gnomic analysis; Microsatellite loci; COI gene sequence